Mendorong Perilaku Wirausaha Muda melalui Efikasi Diri, Sikap, dan Niat Mahasiswa - Tiffany, Tiffany; Ida Puspitowati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of self-efficacy, entrepreneurial attitudes, and perceived behavioral control on the entrepreneurial behavior of students in West Jakarta, with entrepreneurial intention as a mediating variable. This research method uses a quantitative approach with a purposive sampling method on 249 students from various universities in West Jakarta. Data were collected through questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through SmartPLS 4 software. The results of this study indicate that self-efficacy, entrepreneurial attitudes, and perceived behavioral control have a positive and significant effect on entrepreneurial intention. In addition, entrepreneurial intention is proven to significantly mediate the influence of self-efficacy, entrepreneurial attitudes, and perceived behavioral control on entrepreneurial behavior. The conclusion of this study confirms that to encourage real entrepreneurial behavior, strengthening self-efficacy and positive attitudes is necessary, which in turn will strengthen the intention of students in West Jakarta to act. Keywords: Entrepreneurial Attitude, Entrepreneurial Behavior, Entrepreneurial Intention, Perceived Behavioral Control, Self-Efficacy.